The association of acety/ation status with the occurrence of autonomic neuropathy: Diabetic neuropathy cases study - Samekto Wibowo, Samekto Wibowo (Universitas Gadjah Mada, 1999)
Background: Acetylation is a type of drug metabolism pathway. People can be divided into two groups: rapid acetylators, i.e. those who will acetylate drugs (chemical substances) rapidly, and slow acetylators, i.e. those who will acetylate drugs (chemical substances) slowly. Many studies reported that slow acetylator become more succeptable to certain diseases compared to rapid acetylators. Neuropathy might occur in diabetes mellitus, with the following symtoms mononeuropathy, symmetrical peripheral polyneuropathy and/or autonomic neuropathy.Objective: To study the association between acetylation status with the occurrence of autonomic neuropathy on diabetic neuropathy cases.Methods: An analytical descriptive study involving 140 patients of diabetic neuropathy was conducted at Sardjito Central General Hospital, Yogyakarta, Indonesia.Results: Schellong Test confirmed a definite sympatic neuropathy in 11 (7,9%) patients. The examination of acetylation status revealed that 68% of patients were rapid acetylators, and 32% patients were slow acetylators. Among the patients with autonomic neuropathy, it was found that 64% were slowly acetylators, whereas only 36% were rapid acetylators. Among the patients without autonomic neuropathy, 30,5% were slowly acetylators, whrereas 69,5% were rapid acetylators: this distribution frequency was similar to the normal population.Conclusion: Slow acetylation status had significant association (p<0,05) with the occurrence of autonomic neuropathy. Key words: acetylation status - autonomic neuropathy - diabetic neuropathy - sympatic neuropathy - Schellong Test